THE PECULIARITIES OF THE SPEECH OF BLIND AND WEAK-SIGHTED CHILDREN AND THE IMPORTANCE OF THEIR STUDY - Rimbayeva Ozoda Bazarbayevna (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
the development of both their cognitive activities in conjunction with the lifestyle of people with developmental disabilities is different from that of their healthy peers. We will provide information in this article about the peculiarities of the nut of blind and weak-sighted children and the importance of their study